2008
DOI: 10.1016/j.matbio.2007.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Increased degradation of extracellular matrix structures of lacrimal glands implicated in the pathogenesis of Sjögren's syndrome

Abstract: Lacrimal glands (LGs) of male non-obese diabetic (NOD) mice display many features of human LGs in patients afflicted with the autoimmune disease Sjögren's syndrome (SS), including the loss of secretory functions and a lymphocytic infiltration into the glands by 4 months of age. So far, research has mainly focused on the intracellular events that are involved in initiating LG dysfunction; however, the impact of SS on extracellular matrix (ECM) structures of the diseased LGs has not yet been determined. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 53 publications
(61 reference statements)
5
58
1
1
Order By: Relevance
“…Moreover recently enhanced degradation of extracellular matrix proteins, reported in the lacrimal glands of nonobese diabetic mice, was implicated in the pathogenesis of dry eye disease in Sjö gren's syndrome. 45 Our results, together with these reports, suggest that an extracellular matrix protein such as TSP-1 is likely to be important in maintaining the functional integrity of lacrimal glands and its absence results in increased cell death in the tissue that incites inflammatory infiltrates and autoimmune response causing further damage with an eventual functional loss, which in turn leads to ocular surface disease of dry eye. Thus our study strongly implicates TSP-1 deficiency in the pathogenesis of an autoimmune disease like Sjö gren's syndrome.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover recently enhanced degradation of extracellular matrix proteins, reported in the lacrimal glands of nonobese diabetic mice, was implicated in the pathogenesis of dry eye disease in Sjö gren's syndrome. 45 Our results, together with these reports, suggest that an extracellular matrix protein such as TSP-1 is likely to be important in maintaining the functional integrity of lacrimal glands and its absence results in increased cell death in the tissue that incites inflammatory infiltrates and autoimmune response causing further damage with an eventual functional loss, which in turn leads to ocular surface disease of dry eye. Thus our study strongly implicates TSP-1 deficiency in the pathogenesis of an autoimmune disease like Sjö gren's syndrome.…”
Section: Discussionsupporting
confidence: 67%
“…7). In combination with the immunohistochemical and histological approaches, diseased lacrimal glands extracellular matrix (ECM) structures including collagen-and elastin-containing fibres in Sjögren's syndrome were examined using the in-tandem detection of 2-photon excitation imaging (Schenke-Layland et al, 2008). It was concluded that the nonlinear optical results were more pronounced than those delineated by histological analysis.…”
Section: Optical Differentiation Of Intrascleral Elastic Fibres From mentioning
confidence: 99%
“…7,[10][11][12] It would then be advantageous to further develop collagen specific microscopic imaging modalities such as second harmonic generation (SHG) imaging microscopy 13 for this purpose. SHG microscopy has already emerged as a highly sensitive/ specific probe of collagen architecture changes in several diseases, including many cancers, 10,11,[14][15][16][17][18] connective tissue disorders, 19,20 and fibroses. 21,22 All these diseases are characterized by changes in alterations of collagen density, fibrillar organization, collagen isoform distribution, and combinations thereof.…”
Section: Introductionmentioning
confidence: 99%